Characterization of DNA Repair Foci in Root Cells of Arabidopsis in Response to DNA Damage - Hirakawa, Takeshi; Matsunaga, Sachihiro (Frontiers in Plant Science, 2019)
As a sessile organism, plants are constantly challenged by diverse environmental stresses that threaten genome integrity by way of induction of DNA damage. In plants, each tissue is composed of differentiated cell types, and the response to DNA damage differs among each cell type. However, limited information is available on the subnuclear dynamics of different cell types in response to DNA damage in plants. A chromatin remodeling factor RAD54, which plays an important role in the exchange reaction and alteration of chromatin structure during homologous recombination, specifically accumulates at damaged sites, forming DNA repair foci (termed RAD54 foci) in nuclei after γ-irradiation. In this study, we performed a time-course analysis of the appearance of RAD54 foci in root cells of Arabidopsis after γ-irradiation to characterize the subnuclear dynamics in each cell type. A short time after γ-irradiation, no significant difference in detection frequency of RAD54 foci was observed among epidermal, cortical, and endodermal cells in the meristematic zone of roots. Interestingly, cells showing RAD54 foci persisted in roots at long time after γ-irradiation, and RAD54 foci in these cells localized to nuclear periphery with high frequency. These observations suggest that the nuclear envelope plays a role in the maintenance of genome stability in response to DNA damage in Arabidopsis roots.